1976
DOI: 10.1051/jphyscol:1976410
|View full text |Cite
|
Sign up to set email alerts
|

METAL-NONMETAL TRANSITION IN Fe- AND Al-DOPED VO2

Abstract: R6sum6.-Les proprietes structurales, electriques, thermo-Clectriques et magnetiques sont determinees dans des monocristaux des systkmes V I-~F~~O Z (X = 0 ... 0.035) et V I-~A~~O~ (X W 0.007) preparks par transport chimique avec TeC14. Les phases M 1, T, M 2 et R apparaissent. Les diagrammes de phases de V I-~M~: + O~ (Me = Fe, AI, Ga, Cr) avec la transition semi-conducteursemi-conducteur T-t M 2 et la transition semi-conducteur-metal M 2 + R sont compares. Les proprietes electriques et thermo-electriques des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
13
2
Order By: Relevance
“…These are the most effective doping elements to reduce the critical temperature as reported from experiments 5,39. In contrast, Fedoping results in greatest volume shrinkage as predicted by our DFT calculations, and the Fe-doping causes the increase in MIT temperature reported from experiments 5,9. In addition, Pan et al suggested that Cr-doping will result in shrinkage of lattice volume, Brown et al observed the increase in transition temperature in Cr-doped VO 2 8,40.…”
contrasting
confidence: 45%
“…These are the most effective doping elements to reduce the critical temperature as reported from experiments 5,39. In contrast, Fedoping results in greatest volume shrinkage as predicted by our DFT calculations, and the Fe-doping causes the increase in MIT temperature reported from experiments 5,9. In addition, Pan et al suggested that Cr-doping will result in shrinkage of lattice volume, Brown et al observed the increase in transition temperature in Cr-doped VO 2 8,40.…”
contrasting
confidence: 45%
“…Resistance change through the transition was also up to an order of magnitude larger for the doped sample. The lower transition temperature for the Cr-doped sample is noted, since it is known from resistivity measurements on small bulk crystals with a similar composition, 1,2,14 and also from thermal differential analysis of powdered crystals, 15 that Cr substitution of vanadium causes an increase in the transition temperature in comparison with undoped VO 2 . This is also the case for thin films with much higher Cr content.…”
Section: A Thin Film Characterizationmentioning
confidence: 83%
“…%, a morphotropic transition is caused to a different monoclinic phase, designated M 2 . 1,2 This M 2 phase has also been obtained after high-pressure, high-temperature conversion of the M 1 phase, which can stabilize the M 2 phase by generating a defect structure. 3 Application of a relatively small ($0.1 to 1 GPa) uniaxial stress to pure VO 2 M 1 -phase bulk crystals can also induce the M 2 phase.…”
Section: Introductionmentioning
confidence: 99%
“…The doping of low-valent cations such as Fe 3+ , Cr 3+ at low concentration levels would also push the SMPT toward a lower temperature. However, the doping of low-valent cations in high concentration will reverse the SMPT toward a higher temperature [2,11,14,15,16]. Additionally, the doping of Cr 3+ would cause the width of hysteresis loop to be narrower and became more symmetric [17].…”
Section: A N U S C R I P Tmentioning
confidence: 94%
“…According to the literature, the doping of high concentration of iron and nickel elements would increase the phase transition temperature of VO 2 . However, a small amount of pure Fe and Cr elements would decrease the phase transition temperature [2,14,15,16,17,29]. In this study, we aim to examine the synergistic effects on doping Fe, Cr, and Ni elements together and examine their influence on VO 2 films in their phase transition temperature and temperature-dependent hysteresis loop.…”
Section: A N U S C R I P Tmentioning
confidence: 98%